2020
DOI: 10.21203/rs.2.20006/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific Prevalence of coronary heart disease among Tehranian adult population across different glycemic status: Tehran Lipid and Glucose Study, 2008-2011

Abstract: Background: Coronary heart disease (CHD) is one of the main causes of deaths. Alarmingly Iranian populations had a high rank of CHD worldwide. The current study aimed to assess the prevalence of CHD across different glycemic categories. Methods: This study was conducted on 7,718 Tehranian participants (Men=3427) aged ≥ 30 years from 2008 to 2011. They were categorized based on glycemic status. The prevalence of CHD was calculated in each group, separately. CHD was defined as hospital records adjudicated by an … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In their study, using fasting blood sugar criteria, they found that about 40.40% of the participants had dysglycemia (i.e., impaired fasting plasma glucose or diabetes). This finding is supported by our recent study performed in the metropolitan city of Tehran between 2008 and 2011, which showed that only 62.20% of Tehranian adults had normal glucose tolerance, based on strict criteria [2].…”
Section: Dear Editorsupporting
confidence: 70%
“…In their study, using fasting blood sugar criteria, they found that about 40.40% of the participants had dysglycemia (i.e., impaired fasting plasma glucose or diabetes). This finding is supported by our recent study performed in the metropolitan city of Tehran between 2008 and 2011, which showed that only 62.20% of Tehranian adults had normal glucose tolerance, based on strict criteria [2].…”
Section: Dear Editorsupporting
confidence: 70%
“…More details of TLGS design and enrollment have been reported elsewhere [18]. 5,223 women and 4,330 men aged ≥ 30 years (4,459 women and 3,468 men from phase I and 764 new women and 862 new men from phase II) were enrolled. Participants were excluded if they were single (194 women and 179 men), with CVD at baseline (281 women and 318 men), and with no live births (21 women and 8 men), leading to a total of 4727 women and 3825 men.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Owing to notable incidence, unanticipated nature, and high rate of fatality, SCD is taking into account as a public health concern [4,5]. Coronary heart disease (CHD), with a prevalence of 7.7% among Tehranian adult residents [6], is the structural basis for approximately 70% of all SCD; however, the majority of CHD-related SCD occurs as the initial manifestation of CHD [7]; this is mainly because a great proportion of individuals experiencing SCD are not categorized into high-risk groups based on stratification of former studies [5,7,8]. This issue highlights the need for further investigations to identify the risk factors and high-risk groups for SCD well.…”
Section: Introductionmentioning
confidence: 99%